Hydroxychloroquine overcomes cabergoline resistance in a patient with Lactotroph Pituitary neuroendocrine tumor: a case report - Lin, Shaojian; Han, Changxi; Lou, Xiaohui; Wu, Zhe Bao (Frontiers in Endocrinology, 2022)
Objective: A 22-year-old man complaining erectile dysfunction underwent transsphenoidal surgery for a 2.7 cm sellar mass with total resection and was confirmed at pathology to have a lactotroph pituitary neuroendocrine tumor (PiNET). Postoperatively, the patient’s PRL remained at high level and therefore accepted high-dose dopamine receptor agonist (DA) therapy. After over 3 months of bromocriptine (BRC) (15mg/day) and over 3 years of cabergoline (CAB) (3mg/week) therapy, the patient’s prolactin (PRL) never achieved long-term normalization. He was diagnosed with DA-resistant lactotroph PiNET. Method: In this study, the patient was given hydroxychloroquine (HCQ) (200 mg/d) and CAB (3 mg/w) in combination for four months. His PRL level was tested by blood test every month. Results: Taking the combination therapy of HCQ and CAB, the patient’s uncontrolled PRL level was normalized within one month and was maintained at the normal level thereafter. Pituitary magnetic resonance imaging (MRI) images with enhancement showed no recurrence. The patient also regained normal sexual function. Discussion: This is the first report on the combination of HCQ with CAB for the effective treatment of DA-resistant lactotroph pituitary neuroendocrine tumor in a patient, which might provide a novel treatment strategy for clinical management.